LAPTM4B-YAP loop feedback amplification enhances the stemness of hepatocellular carcinoma - Jianping Liao; Jiahong Wang; Yu Xu; Yong Wu; Meifeng Wang; Qiudong Zhao; Xiaodan Tan; Yan Meng; Lixin Wei; Aimin Huang (iScience, 2023)
Summary: Hepatocellular carcinoma (HCC) is highly heterogeneous, and stemness signatures are frequently elevated in HCC tumor cells to generate heterogeneous subtypes via multidirectional differentiation. However, the mechanisms affecting the regulation of stemness in HCC remain unclear. In this study, we identified that lysosome-associated protein transmembrane-4β (LAPTM4B) was significantly overexpressed in stem-like tumor cell populations with multidirectional differentiation potential at the single cell level, and verified that LAPTM4B was closely related to stemness of HCC using in vitro and in vivo experiments. Mechanistically, elevated LAPTM4B suppresses Yes-associated protein (YAP) phosphorylation and ubiquitination degradation. In turn, stabilized YAP localizes to the nucleus and binds to cAMP responsive element binding protein-1 (CREB1), which promotes transcription of LAPTM4B. Overall, our findings suggest that LAPTM4B forms a positive feedback loop with YAP, which maintains the stemness of HCC tumor cells and leads to an unfavorable prognosis for HCC patients.